2022
DOI: 10.1038/s41598-022-04849-0
|View full text |Cite
|
Sign up to set email alerts
|

Petri nets and ODEs as complementary methods for comprehensive analysis on an example of the ATM–p53–NF-$$\kappa$$B signaling pathways

Abstract: Intracellular processes are cascades of biochemical reactions, triggered in response to various types of stimuli. Mathematical models describing their dynamics have become increasingly popular in recent years, as tools supporting experimental work in analysis of pathways and regulatory networks. Not only do they provide insights into general properties of these systems, but also help in specific tasks, such as search for drug molecular targets or treatment protocols. Different tools and methods are used to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In such models, variables usually represent concentrations, levels or the number of molecules of molecular species that are taken into account in a given system. Sometimes, such approaches are expanded by adding a component from other methodologies, like fuzzy logic propositions [35] , or combining dynamics analysis with a parallel one that is concerned with a model structure, not dynamics, as is the case with Petri nets [19] , [48] . Good reviews of these methods can be found in [31] , [50] .…”
Section: Modeling Approaches and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such models, variables usually represent concentrations, levels or the number of molecules of molecular species that are taken into account in a given system. Sometimes, such approaches are expanded by adding a component from other methodologies, like fuzzy logic propositions [35] , or combining dynamics analysis with a parallel one that is concerned with a model structure, not dynamics, as is the case with Petri nets [19] , [48] . Good reviews of these methods can be found in [31] , [50] .…”
Section: Modeling Approaches and Methodsmentioning
confidence: 99%
“…Surprisingly, although various modeling approaches have been used to detect key elements in disease-related signaling pathways and have led to numerous promising molecular targets for drugs, recent work shows that the results obtained with different methods do not always overlap [48] . Comprehensive structural and parametric analysis of ATM/p53/NF-κB signaling pathway model based on ODEs and Petri net has been performed and resulted in finding different subsets of important processes that might indicate prospective targets for drugs.…”
Section: Examples Of the Use Of Petri Netsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, such approaches are expanded by adding a component from other methodologies, e.g., fuzzy logic [95], Petri nets, [96] or others [97].…”
Section: General Modeling Remarksmentioning
confidence: 99%
“…PNs have a broad application in the modeling of biological systems [26][27][28]. PNs have been extended with fuzzy logic approaches in the context of gene regulatory network modeling [29], and have been combined with ODEs to model signaling networks [30]. In the field of biological PN models, the analysis of invariants has proven valuable in application such as gene regulation [31], signal transduction [32][33][34][35][36], and metabolic networks [37,38].…”
Section: Introductionmentioning
confidence: 99%